2018
DOI: 10.3390/su10113841
|View full text |Cite
|
Sign up to set email alerts
|

Does the Impact of China’s Outward Foreign Direct Investment on Reverse Green Technology Process Differ across Countries?

Abstract: The reverse technology spillover effect of Outward Foreign Direct Investment (OFDI) has been widely discussed. In the context of pursuing green growth, a few scholars began to study the impact of OFDI on home country green technological progress or green total factor productivity. However, few of these papers have made a thorough analysis of how OFDI affects the home country’s green technological progress, and have not considered the impact of different types of OFDI on green technological progress. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…By adopting dynamic and static panel models, Zhu and Ye ( 2018 ) examined that OFDI has not significantly improved the Chinese environment. However, Eskeland and Harrison’s ( 1997 ) study analysed that outward FDI helps improve the environmental quality of the host and home countries by encouraging more pollution avoidance effects and green investment.…”
Section: Methodsmentioning
confidence: 99%
“…By adopting dynamic and static panel models, Zhu and Ye ( 2018 ) examined that OFDI has not significantly improved the Chinese environment. However, Eskeland and Harrison’s ( 1997 ) study analysed that outward FDI helps improve the environmental quality of the host and home countries by encouraging more pollution avoidance effects and green investment.…”
Section: Methodsmentioning
confidence: 99%
“…By adopting dynamic and static panel models, Zhu et al (2018) examined that OFDI has not significantly improved the Chinese environment. However, Eskeland and Harrison (1997) study analysed that Outward FDI helps improve the environmental quality of the host and home countries by encouraging more pollution avoidance effects and green investment.…”
Section: Methodsmentioning
confidence: 99%
“…From the perspective of a country's openness to the outside world and international trade, Cao and Wang (2017) pointed out that international trade will affect labor capital ratio and research and development (R&D) costs and increasing import trade with developed countries will improve talent innovation ability and promote green technology progress. From the perspective of the spillover effect of foreign direct investment, Zhu and Ye's (2018) empirical study, utilizing a global Malmquist-Luenberger index, found that foreign direct investment in developed countries will significantly advance green technology innovation, although they observed regional heterogeneity in the impact of foreign direct investment. It can be concluded that the driving forces behind green technology progress are diverse.…”
Section: Literature Reviewmentioning
confidence: 99%